Regulation and Investment in Network Industries: Evidence from European Telecoms - Michał Grajek; Lars-Hendrik Röller (European School of Management and Technology (ESMT), 2009)
We provide evidence of an inherent trade-off between access regulation and investment incentives in telecommunications by using a comprehensive data set covering 70+ fixed-line operators in 20 countries over 10 years. Our econometric model accommodates: different investment incentives for incumbents and entrants; a strategic interaction of entrants' and incumbents' investments; and endogenous regulation. We find access regulation to negatively affect both total industry and individual carrier investment. Thus promoting market entry by means of regulated access undermines incentives to invest in facilities-based competition. Moreover, we find evidence of a regulatory commitment problem: higher incumbents' investments encourage provision of regulated access.
urn:nbn:de:101:1-201106143606
Keywords: C51; L59; L96; 650; telecommunications; access regulation; unbundling; investment; Telekommunikation; Netzregulierung; Entflechtung; Investition; Ökonomischer Anreiz; Telekommunikationsnetz; Telekommunikationspolitik; Welt